Pengelolaan Koperasi Pondok Pesantren Mahasiswa AL Hikam Dalam Bingkai Akuntabilitas: Perspektif Sharia Enterprise Theory - Aviani Widyastuti; Moh Miftachul Fadhli; Sri Wibawani Wahyuning Astuti (Jurnal Akademi Akuntansi, 2022)
Accountability problems and fraudulent practices often occur not only in business sector organizations but also in public sector organizations (non-profit) which are mostly carried out by internal parties. The low credibility and accountability of companies in carrying out conventional accounting is the impact of secular and materialist capitalism. In fact, accountability is a form of agent's responsibility to the principal that must be maintained. Islam also emphasizes accountability as the soul of sharia accounting whose concept is related to God, humans, and the universe (accountability trilogy). Sharia Enterprise Theory (SET) is an implementation that involves the role of humans as caliphs and 'abd llah in the application of the accountability trilogy. Accountability in cooperative management is very important to create credibility and gain public trust. This study aims to analyze the implementation of accountability in the management of the Student Boarding School Cooperative Al Hikam Malang (Koppontren) based on the Sharia Enterprise Theory (SET) perspective. This research is a qualitative descriptive study with observation, interview, and documentation techniques regarding accountability based on various indicators and assessed by a scoring system. The results show that Koppontren has implemented accountability with SET properly in its management, starting from the halal of all aspects of the business, paying attention to muamalah rules, spending zakat, providing social assistance, and always keeping the environment clean. Overall, the percentage of accountability according to the SET perspective obtained is 87%, with details of accountability to humans at 100%; accountability to nature at 67%; accountability to God at 67%; and holistic accountability at 100%.